Remotely delivered cognitive therapy for social anxiety disorder in adolescence: Preliminary efficacy evidence based on changes throughout treatment - Vagos, Paula; Figueiredo, Diana Vieira; Ganho-Ávila, Ana; Mayr, Andreas; Rijo, Daniel (Frontiers in Psychology, 2023)
Cognitive therapy has been established as the frontline treatment for adults with social anxiety disorder (SAD); its efficacy with socially anxious adolescents is incipient but promising. This work investigated change in social anxiety symptoms reported by adolescents and their therapist as they go through remotely delivered 10-session cognitive therapy (i.e., CT@TeenSAD). Participants were 21 adolescents (81% girls; Mage = 16.10) diagnosed with SAD. They reported on change on their social anxiety symptoms at the beginning of each session; their therapist reported on how their symptoms had improved at the end of each session. Results, though preliminary, show that sessions had a significant impact on self- and therapist reported change, with consistent and continuous improvement across intervention sessions. Gender did not impact on that change, but therapist did: though the same pattern of change emerged for both therapists, it was more evident for the therapist with the greatest previous clinical experience. Overall, current findings align with the cognitive therapy framework of progressive gains throughout therapy. They also add evidence on the applicability and usefulness of an online cognitive approach to adolescents diagnosed with SAD.